Project Management Professional (PMP) - Jones, Michelle; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"PMP for project managers is the most sought after industry-recognized certification. The PMP certification is recognized globally. It demonstrates your abilities, experience, education and of course competency to lead and direct projects. PMI offers a comprehensive certification program for practitioners with different levels of education and experience. Project Management Professional (PMP) certification for experienced Project Managers. The PMP certification scheme is accredited by the American National Standards Institute (ANSI) against the International Organization for Standardization (ISO) 17024. Prerequisites For PMP Certification Secondary degree (high school diploma, associate's degree or the global equivalent), 7,500 hours leading and directing projects, 35 hours of project management education OR Four-year degree , 4,500 hours leading and directing projects, 35 hours of project management education."--Resource description page.
Presenter, Michelle Jones.
Title and publication information from resource description page (Safari, viewed February 21, 2017).
Keywords: Project management -- Examinations -- Study guides; Project management -- Examinations, questions, etc; Electronic books